Comparison of infiltration (INF) and inferior alveolar nerve block (IANB) injection techniques in bilateral therapeutic removal of mandibular premolars - Balamurugan Rajendran; Sahana Pushpa Thaneraj (Tabriz University of Medical Sciences, 2021)
Background. The present study aimed to evaluate and compare the anesthetic effect of infiltration (INF) and inferior alveolar nerve block (IANB) techniques for bilateral therapeutic extraction of mandibular premolars. Methods. One hundred patients requiring bilateral therapeutic removal of mandibular premolars were included in the study. For the extraction of the mandibular right premolar tooth, INF was used, and after one week, the mandibular left premolar tooth was extracted using the IANB. The effect of anesthesia between the two techniques was compared and evaluated by ANOVA using SPSS. Results. INF was successful in 78% of cases, whereas IANB was successful only in 22% of cases. Furthermore, INF had a significantly better anesthetic effect than IANB (P<0.05). During pain assessment during the anesthetic drug injection and the procedure, two patients in the INF and five patients in the IANB group reported minimal pain during extraction (P>0.05). The onset of the anesthetic effect was faster in the INF group, while the duration of the effect was longer in the IANB group. Conclusion. INF was a more efficacious local anesthetic technique with high success rate than the IANB technique.